Incidence Analysis of Recurrent Milk Fever in Korean Domestic Dairy Cattle - Ryoung-Hoon Jeon; Gyu-Jin Rho (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Milk fever is a metabolic disease with manifestation of clinical signs due to hypocalcemia, which usually occurs within 48-72 h after delivery. However, even after a successful treatment of milk fever, recurrence of milk fever may occur, and studies on recurrent milk fever are still lacking. Accordingly, the present study was conducted for the purpose of identifying the characteristics of recurrent milk fever according to farm, season, parity, and dystocia that can cause physiological changes in the mother during peri- and postpartum periods. The analysis results showed that the incidence rate of initial and recurrent milk fever according to breeding farm was 5.7%-14.1% and 3.1%-7.2%, respectively, demonstrating a positive correlation between the initial and recurrent milk fever (r = 0.613, p < 0.01). With respect to season, the incidence rate of initial and recurrent milk fever during summer was 12.3% and 7.5%, respectively, which were significantly higher than that of other seasons (p < 0.05). In addition, the recurrence rate, the ratio of recurrence relative to initial milk fever, was highest during summer with 62.7%. Regarding parity, the incidence rate of initial and recurrent milk fever in 3rd parity was 11.1% and 5.8%, respectively, which was significantly higher than in 1st and 2nd parity (p < 0.05). Furthermore, the recurrence rate in 4th parity was 64.1%, showing a pattern of increase in incidence rate with increase in parity. Finally, there were no differences in the incidence rate of initial and recurrent milk fever according to eutocia and dystocia. The findings indicated that the incidence rate of initial milk fever should be reduced to effectively prevent the recurrent milk fever, while animals with 3rd parity or higher should be expected to occur high rate of recurrent milk fever, especially during summer, and the necessary preparations should be made for intensive treatment of such individuals.